Effect of Formulation Variables on Fabrication of Risperidone Loaded Nanoparticles for Sustained Drug Delivery - Gohil, Dipti; Shah, Nirmal; Maheshwari, Rajesh A. (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/ Background: Risperidone, an atypical antipsychotic agent, is used in the treatment of psychotic disorders due to its lower Extra Pyramidal side Effects (EPS) than conventional antipsychotics. Materials and Methods: The objective of the present investigation is to study the effect of formulation variables using 32 factorial design; on preparation of nanoparticles to provide sustained drug release for a prolonged period of time; enhancing therapeutic efficacy by reducing dose dependent side effects. Study include formulation of nanoparticles by the nanoprecipitation method and optimization of the formulation parameters such as Amount of Polymer and Surfactant concentration as independent variables and Particle size and % entrapment efficiency as dependent variables using design of experiment; a statistical tool. Results: Optimized formulation of nanoparticles was characterized for various physicochemical parameters. The particle size was found to be 213.3 nm with 82.89% drug entrapment. Conclusion: In vitro drug release study and Pharmacodynamic study portend promising results of drug delivery for longer duration.
Keywords: Schizophrenia; Risperidone; Nanoparticles; 32 factorial design; Catalepsy